The effect of adding 5% sugar beet on blood pH, glucose concentration and ketone bodies to prevent pregnancy toxemia in Shami goats (Journal of Hama University, 2026)
SummaryThe study was conducted on 20 pregnant female Shami goats at the Research Center affiliated to the Agricultural Scientific Research Authority aged between 2-4 years, and their health status (BCS) between 3 degrees, and their average weight was 60 kg for the year  2023-2024. They were divided into two groups, each group /10/ pregnant females, the first without adding sugar beet to their diet, and the second group with adding sugar beet added at rate of 5% to their ex-goat. Blood samples were collected from them to measure their acidity (pH), and blood sugar and Beta hydroxy butyric acid (BHB) were analyzed in periods one month before birth, two weeks before birth, and two weeks after birth. The differences between the blood indicators of both groups were studied statically. The glucose concentration in the first group (96.33±3.72) mg/dl was higher compared to the second (94.16±8.25) mg/dl in the prenatal stage by one month, while a significant decrease (P≤ 0.05)was observed in the glucose concentration (66.66±6.59) mg/dl in the first compared to the second (76.5±6.59) mg/dl in the prenatal stage by two weeks. The decrease in glucose concentration continued after two weeks of birth in the first  (74.00±7.09) mg/dl and the second (83.66±5.95) mg/dl without any significant differences. While the concentration of ketone bodies was significantly higher (P≤ 0.05) in the first group (1.21±0.49) mmol/l compared to the second (0.55±0.22) mmol/l, and the blood PH value decreased significantly (P≤ 0.05) in the first group (7.33±0.01) compared to its value in the second  (7.39±0.04)  in the stage before birth by one month, and in the  stage before birth by two weeks, the concentration of ketone bodies increased significantly (P≤ 0.001) in the first (4.00±0.09) mmol/l compared to the second  active (1.46±0.80) mmol/l, The significant decrease (P≤ 0.05) in the blood PH value continued before in the second (7.31±0.07) compared to the first (7.39±0.02). As for the postnatal stage by two weeks, the concentration of ketone bodies decreased in the first group to the value (1.43±0.59) mmol/l but it was significantly high (P≤ 0.05)than in the second group (0.53±0.20) mmol/l and an increase in the blood Ph value in the first group (7.41±0.02) and  the second (7.43±0.02) without showing any significant differences in the blood of both groups. This study concludes that adding 5% sugar beet has a good effect in preventing metabolic acidosis and maintaining good gglucos concentration values and reducing the amount of ketone bodies formed in its organs, thus reducing the incidence of pregnancy toxemia and preventing it in pregnant Shami goats in the perinatal period.
Keywords: Key Word: sugar beet, pregnancy toxemia, Shami goat.